The ^135Cs(n,γ) cross section at 30 and 500 keV - Patronis, N.; Assimakopoulos, P. A.; Dababneh, S.; Heil, M.; Kaeppeler, F.; Karamanis, D.; Koehler, P. E.; Plag, R. (HNPS Advances in Nuclear Physics, 2021)
The neutron capture cross section of the unstable isotope ^135Cs was measured relative to that of gold by means of the activation method. The sample was produced by ion implantation in a high resolution mass separator and irradiated with quasi-monoenergetic neutrons at 30 keV and 500 keV, using the ^7Li(p,n)^7Be reaction. After the irradiations at the above energies, one more irradiation with thermal neutrons was used for defining the sample mass and for measuring the half-life of ^136Cs. The neutron capture cross section was determined as 164 ± 10 mbarn and 34.8 ± 3.0 mbarn at 30 keV and 500 keV, respectively, and were used to normalize the theoretically derived cross section shape.